PENGARUH PERBANKAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2014-2023 - Yudianto, Yuda; Setiawan, Iwan; Edman Syarief, Mchamad (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Indonesia is a country with a financial services sector that consists of two working principles, namely conventional and sharia. The sharia financial sector can play a role in encouraging the country's economic growth, especially through sharia banking savings and financing services. The aim of this research is to examine and analyze the influence of total assets, Disbursed Financing (PyD), Third Party Funds (DPK), Return On Assets (ROA) on Indonesia's economic growth for the period 2014 - 2023. This research uses secondary data from Sharia Banking Statistics (SPS) from the first quarter of 2014 to the fourth quarter of 2023 and economic growth data is measured using Gross Domestic Product (GDP) data from the Indonesian Central Statistics Agency (BPS). The data processing technique used in this research is multiple linear regression using Eviews version 12 software to determine the relationship between the independent variable (X) and the dependent variable (Y). The results of the research show: Partially Total Assets, DPK, and PyD have a positive and significant influence on ROA, the Total Assets variable has a positive and significant influence on Indonesia's economic growth, the PyD variable has no positive and significant influence on Indonesia's economic growth, the DPK variable has negative and significant influence on Indonesia's economic growth, the ROA variable has a positive and significant influence on Indonesia's economic growth.